Media Permainan Ular Tangga dalam Mereduksi Kecanduan Game Online di Sekolah Dasar - Sofiyanti, Meitami; Wahyuningsih, Lenny; Rahmawati, Rahmawati; Nurmala, Meilla Dwi; Wibowo, Bangun Yoga (Indonesian Journal of Educational Counseling, 2024)
Online game addiction is a common problem among students. This study aims to determine the effect of using the Snakes and Ladders game in reducing online game addiction among 5th-grade students at SD Negeri Serang 3. An experimental method with a nonequivalent control group design was used. The results showed that the experimental group, which received the Snakes and Ladders game intervention, experienced a significant reduction in online game addiction compared to the control group. The average pretest score for the experimental group was 75.6, and the posttest score was 58.3. The t-test showed t-value -5.669 with Sig. < 0.05, thus accepting Ha. The Snakes and Ladders game is effective in reducing online game addiction among elementary school students.